Oral anticoagulation continuation compared with heparin bridging therapy among high risk patients undergoing implantation of cardiac rhythm devices - Feng, Lei; Li, Yang; Li, Jian; Yu, Bo (Thrombosis and Haemostasis, 2012)
It was the objective of this study to systematically compare the effects of oral anticoagulation (OAC) with heparin bridging therapy among patients at high risk for thromboembolism undergoing implantation of cardiac rhythm devices. A systematic search of PubMed/MEDLINE, Ovid and Elsevier, and the Cochrane Library databases was conducted. Six trials that met our inclusion criteria were identified and included in the present study. The endpoints of this meta-analysis included pocket haematoma, severe haematoma requiring drainage/revision, thromboembolic events, and length of hospital stay. Data were expressed as odds ratios (ORs) and 95% confidence interval (CIs). There was a statistically significant reduction of pocket haematoma (OR 0.29, 95% CI: 0.17 to 0.49, p<0.00001) and haematoma drainage/revision (OR 0.15, 95%CI: 0.04 to 0.54, p=0.004), respectively, in the OAC continuation group versus the heparin bridging group. We did not detect any statistically sig- nificant differences of thromboembolic events (OR 0.48, 95%CI: 0.07 to 3.54, p=0.48) in the two groups. There was a trend that patients in bridging group had longer hospital stays. In conclusion, OAC continu- ation had a better risk-beneficial ratio and shorter length of hospital stay, and was more convenient to implement compared with heparin bridging therapy among patients at high risk for thromboembolism undergoing implantation of cardiac rhythm devices.
Keywords: Oral anticoagulation continuation; heparin bridging; cardiac rhythm; devices implantation; meta-analysis